A New Technology-Based Tool for Building Profitable Biodiversity-Conserving Offerings - C. Haas, Timothy (European Journal of Sustainable Development, 2024)
Biodiversity conservation is an essential but too-frequently overlooked dimension of environmental sustainability. Most endangered species live in developing countries. In these countries, sustainable development projects need to leverage efforts to protect biodiversity rather than being at cross-purposes with them. To these ends, this article describes a business plan that has a firm market a biodiversity offering that is profitable and supports a biodiversity project. This project, in-turn, enhances biodiversity. Customers are kept abreast of the project